An overview of the present stability and performance of eor-foam - Hamza, M.F. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Foam flooding technique, commonly known as foam assisted water alternating gas method (FAWAG) has been identified as an effective chemical enhanced oil recovery (CEOR) technique. The ability of EOR-foam to sweep oil in low permeable zones makes it important displacement fluid in the oil industry. However, extreme reservoir conditions such as temperature, pressure and salinity have detrimental effects on the stability and the overall performance of the EOR-foam. Consequently, understanding foam stability and performance under different conditions is crucial for long term oil field application. This paper discusses the current status of the EOR-foam stability, performance and challenges from laboratory studies to field application perspective. The paper also highlights the knowledge gaps which require further research for successful field application.